Individual and interpersonal factors influencing child marriage: A qualitative content analysis study. - Asma Pourtaheri; Mehr Sadat Mahdizadeh; Hadi Tehrani; Jamshid Jamali; Nooshin Peyman (PLoS ONE)
Background Child marriage is one of the public health challenges that has caused increasing concerns in the health and development system. Therefore, this research was conducted to identify individual and interpersonal factors influencing child marriage from the perspectives of stakeholders and informants. Method This qualitative study was conducted using content analysis and an inductive approach from 2023 to 2024 in Bam city, Kerman, Iran. Thirty-six stakeholders (girls who have been married for 15 years, parents, husbands, and informants) were purposively selected. Data were collected through semi-structured interviews and analyzed using the Graneheim and Lundman approach, with the assistance of MAXQDA software. Results After analyzing of the data, individual and interpersonal themes were emerged. The first theme of "individual factors" consisted of biological, psychological, and demographic category with four sub-categories including insufficient cognitive and inferential development, physiological and anatomical features, facing stressful factors in life, and demographic characteristics. The second theme of "interpersonal factors" consisted of family structure with four sub-categories including traditional parenting methods, family values, family breakup, Inefficiency of management and problem-solving in the family, and weak social capital in the family. The category of Ineffective interactions and social support also encompass two sub-categories: Peer pressure and reference groups, and inappropriate care and support relationship between teachers and students. Conclusion The results showed that individual and interpersonal factors are effective on children's marriage. Some individual factors have a biological origin, indicating that increasing girls' awareness of marriage, pregnancy, individual rights, and life skills is one solution that can help reduce early marriage. On an interpersonal level, fostering positive relationships within the family, school, and society, and strengthening the support network can play a crucial protective role for children.